Association of Anti-Ro Antibodies with ECG Abnormalities in Systemic Lupus Erythematosus: A Cross-Sectional Study in a University Hospital - Delkash, Parisa; Abdehagh, Mohammad; Sadeghi, Soheila; Omidi, Fatemeh (Novelty in Biomedicine, 2025)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with various cardiovascular manifestations. Anti-Ro antibodies are commonly found in SLE patients and may contribute to cardiac abnormalities, including electrocardiographic (ECG) changes. This study assessed the association between Anti-Ro antibodies and ECG abnormalities in SLE patients. Materials and Methods: In this cross-sectional study, 85 SLE patients, all positive for Anti-Ro antibodies, were enrolled from a university hospital. Demographic data, clinical features, and 12-lead ECG results were collected. ECG abnormalities were evaluated, including sinus tachycardia, premature ventricular contractions, QRS fragmentation, ST changes, and QT interval prolongation. Data analysis was performed using SPSS version 26, with appropriate statistical tests to compare variables. Results: Among the 85 patients, 6 (7.06%) exhibited sinus tachycardia, 1 (1.18%) had premature ventricular contractions, and 12.94% showed QRS fragmentation. ST elevation was observed in a minority of patients (30.59%), while 88.24% had normal ST depression results. QTc was prolonged in 11.76% of patients. No significant associations were found between Anti-Ro antibodies and specific ECG abnormalities. Conclusion: This study did not find a significant correlation between Anti-Ro antibodies and ECG abnormalities in SLE patients. However, further research with a larger sample size and more in-depth analysis is needed to clarify Anti-Ro antibodies’ role in SLE’s cardiovascular manifestations.